Randomised placebo-controlled trial of rituximab (anti-CD20) in active ulcerative colitis. Issue 11 (6th April 2011) - Leiper, Keith; Martin, Kate; Ellis, Anthony; Subramanian, Sreedhar; Watson, Alastair J; Christmas, Steve E; Howarth, Deborah; Campbell, Fiona; Rhodes, Jonathan M
Abstract : Objective: To assess the safety and efficacy of the B lymphocyte (anti-CD20) antibody, rituximab, in the treatment of steroid-resistant moderately active ulcerative colitis (UC). Methods: A double-blinded, randomised controlled trial with a 2:1 ratio of treatment:placebo (phase II) was carried out in the setting of a University teaching hospital. The subjects comprised 24 patients with moderately active UC who have either failed to respond to conventional corticosteroid therapy or who have relapsed during corticosteroid withdrawal. Five of 8 placebo-treated patients and 12 of 16 rituximab-treated patients were receiving azathioprine, 6-mercaptopurine or methotrexate. Two infusions of rituximab 1 g in 500 ml of 0.9% saline intravenously over 4 h (n=16) or saline placebo (n=8) were given at 0 and 2 weeks. Patients still receiving corticosteroids on entry (placebo group 7/8; rituximab group 14/16) continued a standard steroid tapering regimen. The primary end point was remission (Mayo score ≤2) at 4 weeks. Secondary end points included response (Mayo score reduced ≥3) at 4 and 12 weeks. Results: Mayo score at entry was higher in rituximab-treated patients (mean 9.19; 95% CI 8.31 to 10.06) than for placebo patients (7.63; 6.63 to 8.62, p=0.03). At week 4 only 1/8 placebo-treated patients and 3/16 rituximab-treated patients were in remission (p=1.0), but 8/16 rituximab-treated patients had responded compared with 2/8 placebo-treated patients, with a median reduction in Mayo score of 2.5 (rituximab) compared with 0 (placebo; p=0.07). This response was only maintained to week 12 in 4/16. Mucosal healing was seen at week 4 in 5/16 rituximab-treated patients and 2/8 placebo-teated patients (non-significant). Rituximab was well tolerated, with one chest infection, three mild infusion reactions plus one case of (probably unrelated) non-fatal pulmonary embolism. Conclusions: Rituximab has no significant effect on inducing remission in moderately active UC not responding to oral steroids. There was a possible short-term response that was not sustained. Rituximab is well tolerated in UC. Clinical trial number: NCT00261118.